PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP IMPULSE BUYING PADA TOKOPEDIA MASA PANDEMI COVID-19 (Studi Kasus Pengguna Tokopedia Di Karawang) - Kurniasih, Lina; Maulana, Asep (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research was conducted to understand the effect of Celebrity Endorser and Brand Image on Impulse Buying on Tokopedia users in Karawang. This study uses quantitative methods, the research instrument used is a questionnaire distributed to 400 respondents who are residents of Karawang with the majority of respondents aged 15-30 years. Accidental sampling is the chosen sampling technique in data collection. The results of this study indicate that both Celebrity Endorser and Brand Image variables have a significant effect on Impulse Buying.